2014
DOI: 10.1021/ie501231a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zr–Alumina in Production of Polyoxymethylene Dimethyl Ethers from Methanol and Formaldehyde: Performance Tests and Kinetic Investigations

Abstract: Polyoxymethylene dimethyl ethers (PODE n ) converted from methanol and formaldehyde were investigated with alumina supported ZrO2 catalyst in a stainless steel tube fixed-bed reactor within the temperature range from 333 to 433 K and the pressure range from 0.1 to 2.5 MPa. First, results from catalytic performance tests showed that the catalyst γ-Al2O3 containing 4 mol % ZrO2 exhibited the highest activity for PODE n synthesis. The stoichiometry analysis of raw material indicated that ZrO2 modified catalyst h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 16 publications
0
66
0
Order By: Relevance
“…• Activity-based model of the chemical equilibrium: Parameters and correlations for the calcu- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 17 Zhao et al 12 Methanol Aqueous formaldehyde solution Zhang et al, 10,11 This work Table 2: Parameters for the calculation of the mole fraction-based chemical equilibrium constant K x ...…”
Section: Supporting Information Availablementioning
confidence: 99%
See 2 more Smart Citations
“…• Activity-based model of the chemical equilibrium: Parameters and correlations for the calcu- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 17 Zhao et al 12 Methanol Aqueous formaldehyde solution Zhang et al, 10,11 This work Table 2: Parameters for the calculation of the mole fraction-based chemical equilibrium constant K x ...…”
Section: Supporting Information Availablementioning
confidence: 99%
“…2 There is large number of articles (e.g. [7][8][9][10][11][12][13][14][15][16][17][18] ) and patents from China concerning OME, as China is the largest coal producer in the world and is seeking for an option to produce liquid fuels from coal. Synthesis gas may however also be produced from renewable feedstocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers on synthesis of PODE n have focused on catalyst preparation and characterization, and process optimization. Various acidic catalysts, including acidic ionexchange resins Zheng et al, 2013Zheng et al, , 2014Burger et al, 2012), ionic liquids , molecule sieves (Zhao et al, 2011), and solid superacids (Li et al, 2015;Zhang et al, 2014), have been employed in synthesis of PODE n . Burger et al (2012) proposed that water reacts with ethers and form alcohols during the synthesis of PODE n from DMM and trioxane in the acidcatalyzed system.…”
Section: Introductionmentioning
confidence: 99%
“…Burger et al (2012) reported the reaction kinetics of the heterogeneously catalytic formation of PODE n from DMM and trioxane, and proposed an adsorptionbased kinetic model to describe the results. Zhang et al (2014) synthesized PODE n from methanol and formaldehyde solution and proposed a kinetic model based on an elimination mechanism. In our previous work (Zheng et al, 2014), we reported the synthesis of PODE n from DMM and PF over acidic ion-exchange resins and proposed an equilibrium molecular size distribution model based on a sequential reaction mechanism, but did not study the kinetics in detail.…”
Section: Introductionmentioning
confidence: 99%